Intelligent tuning of LQR for Regulating Ball and Beam Balance System - Triawan Nugroho; Mochtar, Fahmi M.; Musthofa, Muhammad B. A.; Syeichu, Muhammad M. (Journal of Intelligent System and Telecommunication, 2024)
The ball and beam systems are widely utilized to test and demonstrate the performance of several control methods. However, regulating the ball and beam system is challenging since its inherent instability and nonlinear dynamic system. In this paper, linear quadratic regulator (LQR) is proposed to regulate the ball and beam system. To get the optimal performance, the genetic algorithm (GA) is utilized for intelligent tuning of the LQR. Furthermore, this research uses MATLAB Simulink for numerical simulation. The results reveal that the system can reach the setpoint with , , and are 0.2644 s, 0.5018 s, and 0.6840 s, respectively. In addition, when the setpoint is changed, the response can follow the setpoint and when the system is given a disturbance, the response can return to the setpoint.